Contributions to knowledge of Laniatores (Arachnida: Opiliones: Grassatores) of the department of Loreto, Peru - Ayala-Apaza, Arli (2021)
In this paper we present an analysis of the state of knowledge and species richness of the Laniatores harvestmen from the department of Loreto, a group of little-known arachnids in the Peruvian Amazon. To do this, relevant literature was reviewed and the collection of the Natural History Museum of the Universidad Nacional Mayor de San Marcos, Lima, Peru was examined. Our results show 72 species distributed in 11 families. Cosmetidae (34 spp.), Cranaidae (11 spp.) and Stygnidae (8 spp.) were the most diverse families. Although there is insufficient information, samples from Samiria River (23 species, 11 families) suggest a very high degree of local endemism, 10 species are restricted only to this locality. With this work, 52 species of Laniatores are added to 19 previously recorded for the Loreto department. Families Biantidae, Samoidae and Stygnommatidae are recorded for the first time in Peru. In addition, 12 new species are reported here for the first time in Peru: Cocholla simoni Roewer, Cynorta marginalis Banks, Discosomaticus cinctus (Perty), Meterginus serratus Roewer, Paecilaemula argentinoi Soares, Sibambea rotunda Roewer, Taito insperatus Kury & Barros, Taito rorschachi Kury & Barros, Ventripila marginata Roewer, Hutamaia plei Tourinho & Mendes, Obidosus boibumba (Villarreal & Pinto-da-Rocha), and Stenostygnus pusio Simon.